2018
DOI: 10.1038/s41386-018-0179-5
|View full text |Cite|
|
Sign up to set email alerts
|

Let’s call the whole thing off: evaluating gender and sex differences in executive function

Abstract: The executive functions allow for purposeful, deliberate, and intentional interactions with the world-attention and focus, impulse control, decision making, and working memory. These measures have been correlated with academic outcomes and quality of life, and are impacted by deleterious environmental events throughout the life span, including gestational and early life insults. This review will address the topic of sex differences in executive function including a discussion of differences arising in response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
144
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(177 citation statements)
references
References 152 publications
13
144
3
3
Order By: Relevance
“…Indeed, a meta-analysis of TIMMS and PISA data from 69 countries by Else-Quest and colleagues (2010) found that while gender differences in numeracy skills in mid-adolescence were typically either small or negligible in magnitude, effect sizes differed by country. Reports of gender differences in EF skills are rare, which may well reflect the lack of major gender differences in cognition evident in several meta-analyses (e.g., Grissom & Reyes, 2019;Hyde, 2016).…”
Section: Ses Executive Functions and Mathmentioning
confidence: 99%
“…Indeed, a meta-analysis of TIMMS and PISA data from 69 countries by Else-Quest and colleagues (2010) found that while gender differences in numeracy skills in mid-adolescence were typically either small or negligible in magnitude, effect sizes differed by country. Reports of gender differences in EF skills are rare, which may well reflect the lack of major gender differences in cognition evident in several meta-analyses (e.g., Grissom & Reyes, 2019;Hyde, 2016).…”
Section: Ses Executive Functions and Mathmentioning
confidence: 99%
“…Conversely, male strategies changed frequently and were more influenced by the 28 stochastic rewards. Individual strategies were related to sex-gated changes in neuronal activation Introduction 32 33 Sex differences have been identified in many studies of reward-guided decision-making, seen 34 across multiple mammalian species, and gender differences have been reported in humans (1)(2)(3)(4)(5). 35 In some tasks males acquire more total rewards than females, a result that is sometimes 36 interpreted as a male advantage in learning (6, 7).…”
mentioning
confidence: 99%
“…(43,45,46). Conversely, energy-conserving and habitual 382 behaviors are more prevalent in female animals, including during foraging (1,2,47). Gonadal 383 hormones, such as ovarian hormone estradiol (E2), are thought to exert modulatory control over 384 cost/benefit decision-making that increased E2 resulted in reduction of high-effort choices (5, 48, 385 49).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…latencies) (75). Relevant to this, Grissom et al (2019) conducted an extensive 735 review of sex differences in several aspects of executive function, including attention, and did not 736 find evidence to support robust sex differences in this domain. Prior studies have reported that 737 male rodents show higher levels of novelty-seeking (76), with higher novelty-seeking related to 738 higher levels of impulsivity in males relative to females (77).…”
Section: Sex Differences In Pretraining and Reversal Learning 727mentioning
confidence: 97%